Magnetofluiddynamics in channels and containers - Muller U; Buhler L (Berlin Springer-Verlag, 2001)
This book serves as an introduction to magnetohydrodynamics (MHD) for graduate and advanced undergraduate engineering students. It may be used by engineers and physicists in research institutions and industry to become familiar with the particular phenom
Keywords: Magnetohydrodynamics